The Relationship Between Academic Performance and Reading Ability among Grade 7 Students - Buraga, Carlos (Journal of Interdisciplinary Perspectives, 2025)
This study addressed the issue of poor reading comprehension among Grade 7 students in the City Division of Makati, which directly impacted their academic performance across core subjects. The research aimed to examine the relationship between students' reading ability and academic achievement and develop an intervention program to support struggling readers. A descriptive-correlational research design was employed, and data were gathered from a stratified sample of students to ensure representation across different schools. Reading ability was assessed using standardized tests, which measured decoding, vocabulary understanding, inferencing, and overall comprehension skills. Academic performance was measured through students' final English, Science, Mathematics, and Araling Panlipunan grades. Trained teachers administered the assessments during scheduled sessions to ensure consistency and reliability in the data collection process. The results revealed a significant positive correlation between reading proficiency and academic performance. Students with higher reading comprehension consistently performed better academically than those with lower reading skills. These findings underscore the importance of reading as a foundational skill that impacts learning across all subjects. The study concluded that a comprehensive reading intervention program was necessary to address literacy gaps. The program should focus on differentiated instruction tailored to individual student needs, employ teacher-led reading strategies, and include regular formative assessments to track progress. To ensure effective implementation, the intervention should be integrated into the regular curriculum, supported by ongoing teacher training, and periodically evaluated for impact. The proposed program holds the potential to enhance reading comprehension and, in turn, significantly improve academic achievement for junior high school learners. By addressing students' literacy challenges, this intervention could foster long-term academic success and better prepare students for future educational demands.